2016
DOI: 10.1002/cssc.201600281
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Norbornadiene Compounds for Solar Thermal Storage by First‐Principles Calculations

Abstract: Molecular photoswitches capable of storing solar energy are interesting candidates for future renewable energy applications. Here, using quantum mechanical calculations, we carry out a systematic screening of crucial optical (solar spectrum match) and thermal (storage energy density) properties of 64 such compounds based on the norbornadiene-quadricyclane system. Whereas a substantial number of these molecules reach the theoretical maximum solar power conversion efficiency, this requires a strong red-shift of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 43 publications
4
41
0
Order By: Relevance
“…The shift of the absorption spectrum with the strength of the donor species is in line with our earlier calculations 10, 15. More interesting in the present context is the strong enhancement of the dipole oscillator strength (Table 5) that results from insertion of an ethynyl bridge on going from 4 a to 5 , and gives rise to a large increase in the extinction coefficient.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The shift of the absorption spectrum with the strength of the donor species is in line with our earlier calculations 10, 15. More interesting in the present context is the strong enhancement of the dipole oscillator strength (Table 5) that results from insertion of an ethynyl bridge on going from 4 a to 5 , and gives rise to a large increase in the extinction coefficient.…”
Section: Resultssupporting
confidence: 91%
“…The spectra were subsequently obtained by averaging over the isomers weighted by their respective Boltzmann factors 15. All calculations were carried out using the NWChem 6.5 software package 31…”
Section: Methodsmentioning
confidence: 99%
“…Through this work, it was also found that the properties of NBD20 were much better than expected, as it appeared that the acetyl group causes additional broadening the absorbance peak, giving a better onset of absorbance; unfortunately, the attractive optical absorption properties were counterbalanced by a low quantum yield of 28 %. The kinetic data for NBD20 was interesting, having a ketone as an acceptor in conjunction with an anisole donor, where QC20 had a half‐life over one year at 25 °C, compared to less than four days for QC19 , which went against the trend typically found for NBD derivatives of this type and this observation verifies our earlier suggestion that broadening of the main optical transition could be an effective way to improve the absorption properties of this type of system. In summary, the 1,4‐triazole functionalizations were preferable over the 1,5‐triazole pattern, leading to NBD‐QC photoswitches with excellent thermal stability.…”
Section: Discussionsupporting
confidence: 81%
“…In the cases where the initial method did not work, this was supplemented by the reported procedure employing a palladium‐catalysed Suzuki reaction upon 2‐chloro‐3‐cyanonorbornadiene . A recent theoretical study showed that certain aromatic donor units could enhance the MOST properties, including dimethylaniline and thiophene, among other electron rich substituents, which were accordingly included in this series . Figure shows the X‐ray crystal structure for NBD2 h , which during the course of this investigation was shown to possess excellent absorption properties (additionally, the structure of NBD2 b can be found in the Supporting Information).…”
Section: Figurementioning
confidence: 99%